First‐in‐Human Phase I Study of Envafolimab, a Novel Subcutaneous Single‐Domain Anti‐PD‐L1 Antibody, in Patients with Advanced Solid Tumors. (27th May 2021) - Papadopoulos, Kyriakos P.; Harb, Wael; Peer, Cody J.; Hua, Qiong; Xu, Siying; Lu, Haolan; Lu, Ni; He, Yue; Xu, Ting; Dong, Ruiping; Gong, John; Liu, David
Abstract: Lessons Learned: Subcutaneous injection was an effective route of administration for envafolimab with a favorable pharmacokinetic profile in patients with previously treated advanced solid tumors. Subcutaneous envafolimab was well tolerated and had durable antitumor activity at a wide range of doses and schedules. Envafolimab has the potential to be a more convenient option than currently approved intravenous PD‐1/PD‐L1 inhibitors. Background: Envafolimab is a novel fusion of a humanized single‐domain PD‐L1 antibody and human IgG1 Fc fragment formulated for subcutaneous injection. This study explored the safety and feasibility of subcutaneous administration of envafolimab as an alternative to intravenous administration of PD‐1/PD‐L1 inhibitors in the treatment of advanced, refractory solid tumors. Methods: This was a first‐in‐human, open‐label phase I trial. In a dose‐escalation phase, patients received subcutaneous envafolimab 0.01–10 mg/kg once weekly following a modified 3+3 design. In a dose‐exploration phase, patients received subcutaneous envafolimab 300 mg once every 4 weeks. Results: Twenty‐eight patients were enrolled (dose escalation n = 18, dose exploration n = 10, median age 66 years; 71% male; ECOG performance score = 0 [21%] or 1 [79%]). No dose‐limiting toxicities or injection‐site reactions were reported. Envafolimab demonstrated dose‐proportional increases in area under the time‐concentration curve and maximum plasma concentration. Median time to maximum plasma concentration was 4–7 days. In the dose‐exploration phase, terminal half‐life was 14 days after dose 1 in cycle 1 and 23 days at steady state. Three patients experienced a confirmed partial response. Conclusion: Subcutaneous envafolimab had a favorable safety and pharmacokinetic profile, with promising preliminary antitumor activity in patients with advanced solid tumors.